Effectiveness of Implementing Nursing Intervention Health Education About Triage on Patients' Families in The Emergency Room Hospital - Rachmah, Siti; Mawaddah, Nurul; Wijaya, Tri Atma (Al-Hijrah Indonesia, 2025)
The Emergency Department is the leading health service in a hospital institution, providing initial assistance to patients based on the triage concept. A lack of understanding of the concept of triage is one of the factors that cause dissatisfaction with services in the Emergency Department. The research aims to determine the effect of health education about triage on the level of satisfaction of families who come to the Reksa Waluya Hospital Emergency Room. The research design used a quasi-experimental with a post-test only with a control group research design, which involved randomly dividing subjects into control and experimental groups. The total research sample was 50 respondents, with purposive sampling used. The instrument for this research is an educational satisfaction questionnaire sheet regarding triage. The study results showed that families' satisfaction in the ER at Reksa Waluya Hospital regarding triage in the control group was mainly quite satisfied (52%). In the experimental group, the majority were satisfied after being given health education about triage (56%). The results of the Mann-Whitney analysis obtained a significance value of 0.000 (p < 0.05), which shows that there is an influence of health education about triage on the level of satisfaction of patient families in the ER at Reksa Waluya Hospital, Mojokerto. The importance of providing health education for families and patients regarding the triage process can provide an overview and understanding, so that satisfaction with services can increase, avoid excessive complaints, and ensure that services in the emergency room will not be disrupted.